2020
DOI: 10.1093/treephys/tpaa078
|View full text |Cite
|
Sign up to set email alerts
|

Coexpression analysis of a large-scale transcriptome identified a calmodulin-like protein regulating the development of adventitious roots in poplar

Abstract: Poplars are important woody plants, and the ability to form adventitious roots (ARs) is the key factor for their cultivation because most poplars are propagated by cloning. In previous studies, Ca2+ was confirmed to regulate AR formation in poplar. In this study, wild type poplar cuttings grown in 1.0 mM Ca2+ solution showed the best visible performance of AR development. Coexpression analysis of a large-scale RNA-Seq transcriptome was conducted to identify Ca2+-related genes that regulates AR development in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 48 publications
0
15
0
Order By: Relevance
“…By combining transcriptomic and metabolic data analyses, genes for some metabolite biosynthesis pathways could be identified. The mechanism for the prediction is based on metabolite accumulation correlating with the expression of the corresponding gene, and this mechanism has been tested in a number of previous reports, such as coexpression analyses in poplar and Arabidopsis. In this study, we mainly focused on biosynthesis pathways for fatty acids, raffinose, and HTs. Four, 3, and 12 genes were predicted to be involved in the biosynthesis of these metabolites, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By combining transcriptomic and metabolic data analyses, genes for some metabolite biosynthesis pathways could be identified. The mechanism for the prediction is based on metabolite accumulation correlating with the expression of the corresponding gene, and this mechanism has been tested in a number of previous reports, such as coexpression analyses in poplar and Arabidopsis. In this study, we mainly focused on biosynthesis pathways for fatty acids, raffinose, and HTs. Four, 3, and 12 genes were predicted to be involved in the biosynthesis of these metabolites, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The detailed procedures for A. rhizogenes strain K599 transformation are similar to those of previous studies in which poplar was transformed with Agrobacterium. tumefaciens. , Leaf explants of poplar cv. “Shanxinyang” were inoculated with a suspension of K599 strains harboring expressed SDH , UGT genes, or the empty 2301S plasmid.…”
Section: Methodsmentioning
confidence: 99%
“…In the absence of Ca in the media, only 55% of cuttings from the hybrid aspen P. tremula × P. tremuloides developed ARs and the addition of LaCl 3 , a calcium channel blocker, completely inhibited rooting in these cuttings (Bellamine et al, 1998). Recently, Xiao et al (2020) showed that poplar cuttings grown FIGURE 2 | Factors affecting adventitious root formation in Populus. The genotype the mother plant will have an effect on the ability of the cutting to root.…”
Section: Mineral Nutrition: Macro and Micronutrientsmentioning
confidence: 99%
“…In the absence of Ca in the media, only 55% of cuttings from the hybrid aspen P. tremula × P. tremuloides developed ARs and the addition of LaCl 3 , a calcium channel blocker, completely inhibited rooting in these cuttings ( Bellamine et al, 1998 ). Recently, Xiao et al (2020) showed that poplar cuttings grown on hydroponic solutions added with 1 mM of Cl 2 Ca significantly increased the AR length and fresh weight, whereas 6 mM had the opposite effect. These results confirm that Ca regulate late phases of AR formation in Populus .…”
Section: Environmental Factorsmentioning
confidence: 99%
“…Calmodulin is involved in AR formation by modulating IAA content. A recent study showed that the poplar transgenic lines with overexpressed the calmodulin-like protein (CML) family gene, PdeCML23-1, exhibited more ARs and higher IAA accumulation in cuttings (Xiao et al, 2020). Auxin receptor genes have also been demonstrated to be involved in AR formation.…”
Section: Auxin Synthesis- Homeostasis- and Receptor-related Genes Mediate Ar Formationmentioning
confidence: 99%